2021
DOI: 10.5194/amt-2021-115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosgene distribution derived from MIPAS ESA v8 data: intercomparisons and trends

Abstract: Abstract. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) measured the middle-infrared limb emission spectrum of the atmosphere from 2002 to 2012 on board ENVISAT, a polar-orbiting satellite. Recently, the European Space Agency (ESA) completed the final reprocessing of MIPAS measurements, using Version 8 of the Level 1 and Level 2 processors, which include more accurate models, processing strategies and auxiliary data. The list of retrieved gases has been extended, it now includes a number… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Deviations in the tropics are quite large. The deviations are in line with the findings of Pettinari et al (2021), who compared v8 data not only to MIPAS-B but also to observations from ACE-FTS. Pettinari et al (2021) found that some of the differences between MIPAS-E and MIPAS-B can be attributed to the different spectroscopic data used (Toon et al, 2001, for MIPAS-B andTchana et al, 2015, in the case of MIPAS-E).…”
Section: Nosupporting
confidence: 89%
See 1 more Smart Citation
“…Deviations in the tropics are quite large. The deviations are in line with the findings of Pettinari et al (2021), who compared v8 data not only to MIPAS-B but also to observations from ACE-FTS. Pettinari et al (2021) found that some of the differences between MIPAS-E and MIPAS-B can be attributed to the different spectroscopic data used (Toon et al, 2001, for MIPAS-B andTchana et al, 2015, in the case of MIPAS-E).…”
Section: Nosupporting
confidence: 89%
“…3.9 Additional v8 products: C 2 H 2 , C 2 H 6 , COCl 2 , OCS, and CH 3 Cl Some more target molecules have been operationally processed by the v8 algorithm. To date, an intercomparison study is only available for COCl 2 (Pettinari et al, 2021). Similar to the additional v7 gases, the emissions of spectral lines of the v8 molecules are also weak compared to the spectral signatures of the standard gases (before v7).…”
Section: Nomentioning
confidence: 99%
“…The span of time covered by the database, and the fact that the database has been developed using the last version of MIPAS level-1 data where the calibration errors due to time dependent detector non-linearities have been reduced, will ensure an improvement in the estimation of the trends for the stratospheric and upper tropospheric concentration of the included gases. An example of the studies that can be performed with the MIPAS level2-v8 database is reported in Pettinari et al (2021), where the data of the new retrieved species COCl 2 have been used to study its trends in the UTLS. The data are reported at the vertical grid coincident with the tangent altitudes of the observations, spanning the altitude range from 6 to 68 km in the FR and from 3 to 70 km in the OR.…”
Section: The Mipas Level2-v8 Databasementioning
confidence: 99%